2018
DOI: 10.1103/physrevd.97.123010
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational wave echoes from strange stars

Abstract: It has recently been claimed, with a 4.2σ significance level, that gravitational wave echoes at a frequency of about 72 Hz have been produced in the GW170817 event. The merging of compact stars can lead to the emission of gravitational waves echoes if the post-merger object features a photon-sphere capable of partially trapping the gravitational waves. If the post-merger source is a black hole, a second internal reflection surface, associated to quantum effects near the black hole horizon, must be present to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 59 publications
2
41
0
Order By: Relevance
“…This result is in agreement with the findings of Ref. [35], that we complemented here with a comprehensive analysis of rotation.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This result is in agreement with the findings of Ref. [35], that we complemented here with a comprehensive analysis of rotation.…”
Section: Discussionsupporting
confidence: 94%
“…11 shows that, for these light objects, the detectability of GW echoes must rely on an unphysical EoS as the physical branch ω 1 cannot sustain visible signals. As already noticed in [32] (see also [35]), a compactness extremely close to the Buchdahl limit (at least 10 −2 ) is indeed needed. We remark that this conclusion depends on the value of M chosen to compute the echo frequency In such a case, it would be possible to move the shaded region in Fig.…”
Section: � ��� ��� ��� ��� ���mentioning
confidence: 71%
See 1 more Smart Citation
“…43 has shown that strange stars can emit gravitational wave echoes on the order of tens of kilohertz (see details in Ref. 43 and the references therein). It is obvious from the upper panel of Fig.…”
Section: Mass-radius Relationmentioning
confidence: 99%
“…In the present paper we take quark EOS in general linear form and then we utilized MIT bag model as a special case. We have not used any specific value of bag constants rather we determine all the possible values of bag constants by studying compact 4 stars. The purpose of the paper is not only to provide possible range of B but also to present a general model for strange star with general linear quark EOS.…”
Section: Introductionmentioning
confidence: 99%